2022
DOI: 10.1371/journal.pone.0276689
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the nutritive value of fifteen multipurpose fodder tree species: A case study of north-western Himalayan mid-hills

Abstract: Multipurpose tree species are recognized as an important fodder source for livestock, but their potential remains untapped due to dearth of knowledge about their nutritive value. Therefore, 15 MPTs, i.e., Acacia catechu, Albizia chinensis, Bauhinia variegata, Celtis australis, Ficus roxburghii, Grewia optiva, Leucaena leucocephala, Melia composita, Morus serrata, Olea glandulifera, Ougienia oojeinensis, Pittosporum floribundum, Quercus glauca, Q. leucotrichophora and Salix tetrasperma were evaluated for nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
(94 reference statements)
1
7
0
Order By: Relevance
“…It has been reported that one of the limiting factors for forage production is the low rainfall season (Navale et al 2022), which is consistent with the results of this research. On the other hand, studies carried out on G. ulmifolia and L. leucocephala in tropical forage banks did not show a negative effect on forage yield during the dry season (Casanova-Lugo et al 2014).…”
Section: Biomass Yieldsupporting
confidence: 93%
See 2 more Smart Citations
“…It has been reported that one of the limiting factors for forage production is the low rainfall season (Navale et al 2022), which is consistent with the results of this research. On the other hand, studies carried out on G. ulmifolia and L. leucocephala in tropical forage banks did not show a negative effect on forage yield during the dry season (Casanova-Lugo et al 2014).…”
Section: Biomass Yieldsupporting
confidence: 93%
“…However, the lack of evidence on appropriate cutting or harvest heights can cause a progressive decrease in forage production due to the reduction in the number of stem buds that limit the regrowth of new leaves (Letty et al 2021). Likewise, it causes the depletion of plant reserves, because they mobilise reserve carbohydrates to rebuild photosynthetic tissue after harvest, grazing or seasonal loss of foliage (Navale et al 2022). Therefore, knowing the optimal harvest height of T. diversifolia is essential for the sustainable management of this important forage plant in animal production systems in the tropics (Ruiz et al 2017, Letty et al 2021.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Singh et al (2010; reported that the nutritive values (chemical components) of high altitudinal browse trees were higher than those from the low altitude. Some of the factors that may be responsible for this variation in findings may be due to the season of harvesting of the plants (Navale et al, 2022) and geographical structure, i.e., elevation/topography/altitude (Shah et al, 2019;Elbasiouny et al, 2022). Other possible factors that may cause variation between browse plants grown on low landscapes and high landscapes include daylight, type of soil, precipitation, organic matter contents and temperature among others (Shah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned reservations, combined with public concerns about the safety and quality features of the produced foodstuffs and animals’ welfare [ 5 ], have highlighted the nutritional health of livestock at the forefront of the European Union’s legislative framework [ 6 ]. This functional necessity is influenced by multiple parameters, such as food availability, feed nutritional quality, consumption, digestibility, and feed metabolism [ 7 ]. However, the observed recent disruption of global supply chains has put under question—or significant risk—these vital parameters for the achievement of sustainable production [ 8 ].…”
Section: Introductionmentioning
confidence: 99%